The role of sodium butyrate in modulating growth, intestinal health, and antimicrobial efficacy in turbot (Scophthalmus maximus L.) fed high soy diets - Jinjin Zhang; Cuijing Jia; Jinping Dong; Jingliang Wu; Minggang Liu; Hansong Zhang; Chengshuo Zhao (Scientific Reports)
Abstract Butyrate is one of the most abundant short-chain fatty acids (SCFAs), which are important metabolites of dietary fiber by fermentation of gut commensals, and has been shown to be vital in maintaining host health. The present study mainly investigated how sodium butyrate (NaB) supplementation in the diet with high proportion of soybean meal (SBM) affected turbot. Four experimental diets were formulated: (1) fish meal (FM) based diet (control group), (2) SBM protein replacing 45% FM protein in the diet (high SBM group), (3) 0.2% NaB supplementation in the high SBM diet (high SBM + 0.2% NaB group), and (4) 0.5% NaB supplementation in the high SBM diet (high SBM + 0.5% NaB group). The fish were fed four different diets for 8 weeks. The results showed that the high SBM diet significantly suppressed growth performance, induced typical enteritis symptoms and decreased resistance to bacterial infection. However, inclusion of 0.2% and 0.5% NaB in the high SBM diet both effectively increased the growth performance of turbot. Meanwhile, dietary NaB protected the intestinal morphology, and regulated the gene expression of inflammatory cytokines to relieve the inflammation of turbot, such as TNFα, IL-1β, NFκB and IL-10. Moreover, supplementation with NaB in the high SBM diet activated HIF-1α/IL-22/Lysozyme signaling pathway to against Edwardsiella tarda (E. tarda) infection, especially 0.5% NaB supplementation exerted more effectively to defence bacterial infection under inflammatory state. In conclusion, dietary NaB significantly promoted growth and gut health of turbot. Besides, it enhanced the resistance of fish to bacterial infection, especially dietary 0.5% NaB supplementation.